A Multi‐Pyridine‐Anchored and ‐Linked Bilayer Photocathode for Water Reduction - Tang, Kun; Shao, Jiang‐Yang; Zhong, Yu‐Wu (Chemistry : a European journal, 2023)
The development of efficient photocathodes is of critical importance for the constructions of promising tandem photo‐electrochemical cells. Most known dye‐sensitized photocathodes are prepared with the conventional carboxylic or phosphonic acid anchors and require the presence of other terminal linking groups to connect catalysts; they suffer from high synthetic difficulty and low adsorption stability in aqueous media. Here, a compact bilayer photocathode has been prepared by using a pyrene‐based photosensitizer with multiple terminal pyridine moieties as both the anchoring and linking groups to connect a Co hydrogen‐evolution catalyst to the NiO substrate. The catalyst and dye molecule are assembled in a layer‐by‐layer manner on NiO through the metal‐pyridine coordination. This photocathode exhibits good dye adsorption stability in aqueous media. A stable cathodic photocurrent of 70 μA cm−2 was achieved, with H2 being generated at the photocathode under the visible‐light irradiation. The Faraday efficiency of H2 evolution was estimated to be 9.1 %. Transient absorption spectral studies suggest that the interfacial hole transfer occurs within a few picoseconds. The integration of the organic photosensitizer with pyridine anchoring and linking groups is expected to provide a simple method for the fabrication of stable and efficient photocathodes. NiO Substrate & Co. A photocathode has been prepared by using a pyrene‐based photosensitizer with multiple terminal pyridine moieties as both the anchoring and linking groups to connect a Co hydrogen‐evolution catalyst to the NiO substrate. This photocathode exhibits good dye adsorption and photochemical stability in aqueous solution and is applied in water reduction into hydrogen under irradiation in photo‐electrochemical cells.